PENDIDIKAN KARAKTER PADA ANAK USIA SEKOLAH DASAR (Studi Kasus di Desa Langgahan Kecamatan Kintamani Kabupaten Bangli) - Suyanto, I Nyoman; Sukerni, Ni Made; Muliani, Ni Made (UHN IGB Sugriwa Denpasar, 2024)
Education is a process or effort made by one person to another to increase knowledge from not knowing to knowing, from not understanding to understanding and from not being aware. Through the education obtained, humans can make things through the consideration of their minds and can increase their creativity. In addition, it also increases the natural potential and abilities possessed in accordance with what is expected. In human life, education is the main need to develop all forms of potential in him. The problems to be discussed in this study are: (1) accessing the role of schools in the development of character education in Langgahan (2) knowing the role of parents in developing character education in Langgahan Village (3) accessing the role of the community in developing character education in Langgahan Village. This study aims to determine the role of schools, parents, and the community in character development, and to determine the value of character education from the role of schools, parents and society. This research is examined using the theory of moral development in this study using data collection techniques such as observation, interviews, literature study, documentation. The data that has been collected was analyzed using qualitative descriptive analysis methods. Based on the results of the research and data analysis conducted, it shows that (1) the role of schools in the development of character education in children both through learning and extracurricular activities, (2) the role of parents in developing parental character education as educators in the family and as role models. , (3) in the development of character education in the community through the application of the teachings of Tri Hita Karana such as prahayangan, pawongan and palemahan. The implications of the role of schools, parents and the community in the development of character education in children believe in character, religion, honesty, independence, hard work, tolerance, discipline, responsibility, and care for the environment. Referring to these findings, it can be seen that the role of schools, parents, and the community plays an important role in the success of children and has been running well based on problem analysis with the theory used in this study. Keywords: Character education, Elementary school children, Case study